A complete genomic analysis of hepatitis B virus genotypes and mutations in HBeAg-negative chronic hepatitis B in China - Zhu, L.; Tse, C. -H.; Wong, V. W. -S.; Chim, A. M. -L.; Leung, K. -S.; Chan, H. L. -Y. (Journal of viral hepatitis, 2008)
We aimed to study the distribution of hepatitis B virus (HBV) genotypes/subgenotypes in different parts of China and their clinical impact on the severity of hepatitis B e antigen (HBeAg)‐negative chronic hepatitis B. Residual serum samples from a cohort of HBeAg‐negative chronic hepatitis B patients in Hong Kong, Shanghai and Beijing were studied. Complete HBV genomic sequencing was performed for phylogenetic tree analysis and determination of HBV mutations was carried out. Mutations associated with severe liver fibrosis (Ishak score 4 or more) were selected by computerized information gain criteria. Genotype B (all subgenotype Ba) HBV was present in 19 of 45 (42%), 12 of 31 (39%) and 5 of 25 (20%) patients in Hong Kong, Shanghai and Beijing, respectively (P = 0.16). Ninety‐seven per cent of genotype C HBV in Shanghai and Beijing belonged to subgenotype Ce whereas 69% of genotype C patients in Hong Kong belonged to subgenotype Cs (P < 0.001). Patients infected by subgenotype Cs had the lowest serum albumin and highest alanine aminotransferase levels compared with subgenotype Ce and Ba. Patients infected by subgenotype Cs also had more severe histological necroinflammation than subgenotype Ce. Two HBV mutations were identified to associate with severe liver fibrosis (G2858C and C2289A) and one mutation was protective against severe liver fibrosis (T2201C). The T2201C mutation was found exclusively among patients (21 of 46 patients, 45%) infected by HBV subgenotype Ce. The clinical differences in HBeAg‐negative chronic hepatitis B in China may be influenced by different distribution of subgenotype C HBV.